2004
DOI: 10.1177/070674370404900705
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Function in Alzheimer's Disease: Evidence for Dysfunction and Potential as a Therapeutic Target for the Treatment of Behavioural and Psychological Symptoms of Dementia

Abstract: Alzheimer's disease (AD) is characterized by disruptions in multiple major neurotransmitters. While many studies have attempted to establish whether GABA is disrupted in AD patients, findings have varied. We review evidence for disruptions in GABA among patients with AD and suggest that the variable findings reflect subtypes of the disease that are possibly manifested clinically by differing behavioural symptoms. GABA, the major inhibitory neurotransmitter, has long been a target for anxiolytics, hypnotic seda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(111 citation statements)
references
References 128 publications
4
103
1
2
Order By: Relevance
“…Moreover, activity of surrounding neurons influences survival and maturation of newborn progenitors through tonic GABA activation even before they receive synaptic input (Ge et al, 2006;Overstreet-Wadiche and Westbrook, 2006). Both GABAergic and glutamatergic signaling required for successful maturation and integration of newborn neurons are compromised by late stages of AD (Gsell et al, 2004;Lanctot et al, 2004). Although not studied in our transgenic lines, the degradation of these neurotransmitter systems in other mouse models of AD (Bell et al, 2006) suggests loss of newborn neurons in our APP/PS1 mice may be caused by damage to the microenvironment required for their development and survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, activity of surrounding neurons influences survival and maturation of newborn progenitors through tonic GABA activation even before they receive synaptic input (Ge et al, 2006;Overstreet-Wadiche and Westbrook, 2006). Both GABAergic and glutamatergic signaling required for successful maturation and integration of newborn neurons are compromised by late stages of AD (Gsell et al, 2004;Lanctot et al, 2004). Although not studied in our transgenic lines, the degradation of these neurotransmitter systems in other mouse models of AD (Bell et al, 2006) suggests loss of newborn neurons in our APP/PS1 mice may be caused by damage to the microenvironment required for their development and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Within this critical time window, the formation of new hippocampal circuits and the survival of new neurons are sensitive to neuronal activity in the local environment (Tozuka et al, 2005;Ge et al, 2006;OverstreetWadiche and Westbrook, 2006;Tashiro et al, 2006). Given that altered hippocampal neurotransmitter levels in the AD brain are suggestive of changes in neuronal activity (Gsell et al, 2004;Lanctot et al, 2004), we evaluated the survival of newborn cells in the hippocampus of our transgenic mice during this critical window for survival.…”
Section: Short-term Survival Of Newborn Cells Is Not Altered By Overpmentioning
confidence: 99%
“…Gut microbiota disruption, especially the reduction of Lactobacillus and Bifidobacterium, will influence the production of GABA in the gut and then lead to reduction of GABA in CNS. Postmortem study of AD patients found that the GABA levels were decreased in frontal, temporal and parietal cortex of AD patients (Lanctot et al, 2004;Solas et al, 2015).…”
Section: The Influence Of Gut Microbiota On Neurochemical and Metabolmentioning
confidence: 99%
“…GABA is the major inhibitory neurotransmitter in human CNS. Dysfunction of the GABAergic system may contribute to cognitive impairment (Lanctot et al, 2004). The increase of GABA in the gastrointestinal tract is correlated with the increase of GABA in CNS.…”
Section: The Influence Of Gut Microbiota On Neurochemical and Metabolmentioning
confidence: 99%
“…Stage-specific changes in amyloid plaque and neurofibrillary tangle burden have been documented, 5 as well as changes in neurotransmitters, such as catecholamines, 6,7 GABA, 8 and glutamate. 9 For example, in the cholinergic system (the beststudied of the neurotransmitter systems in AD) cholinergic markers, such as choline acetyltransference (ChAT), do not decline significantly until later stages of AD, while milder stages are characterized by relatively preserved ChAT.…”
mentioning
confidence: 99%